2005
DOI: 10.1080/02699050410001720040
|View full text |Cite
|
Sign up to set email alerts
|

Columnar organization of the mammalian visual cortex and its vulnerability following lesion in adult cats

Abstract: It is well known that in the mammalian visual cortex the neurons, sharing similar response properties, are grouped together into functional units, known as cortical columns. The orientation and ocular dominance columnar organization is a fundamental element for both the anatomical and physiological features of the visual cortex. Nonetheless, little is known about the functional restoration of matured columnar columns following injury. In the present study, the visual cortex of adult cats was studied electrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In contrast, a considerable number of studies have reported minicolumn spacing for a variety of smaller mammals: rhesus macaque temporal cortex (Buxhoeveden and Casanova, 2000;Buxhoeveden et al, 2001a,b); rhesus macaque motor cortex (Amirikian and Georgopoulos, 2003); cat primary somatosensory cortex (Favorov and Diamond, 1990;Tommerdahl et al, 1993); cat visual cortex (Gurshumov and Yinon, 2005); rat somatosensory cortex (Tommerdahl et al, 1993;Joublin et al, 1996;Lubke and Feldmeyer, 2007), and for humans: cingulate and pericingulate cortex (Schlaug et al, 1995); primary auditory cortex (Chance et al, 2006); posterior auditory association region (Buxhoeveden and Casanova, 2000;Buxhoeveden et al, 2001b;Chance et al, 2006). These studies demonstrate that humans have larger minicolumns than other smaller mammals.…”
mentioning
confidence: 90%
“…In contrast, a considerable number of studies have reported minicolumn spacing for a variety of smaller mammals: rhesus macaque temporal cortex (Buxhoeveden and Casanova, 2000;Buxhoeveden et al, 2001a,b); rhesus macaque motor cortex (Amirikian and Georgopoulos, 2003); cat primary somatosensory cortex (Favorov and Diamond, 1990;Tommerdahl et al, 1993); cat visual cortex (Gurshumov and Yinon, 2005); rat somatosensory cortex (Tommerdahl et al, 1993;Joublin et al, 1996;Lubke and Feldmeyer, 2007), and for humans: cingulate and pericingulate cortex (Schlaug et al, 1995); primary auditory cortex (Chance et al, 2006); posterior auditory association region (Buxhoeveden and Casanova, 2000;Buxhoeveden et al, 2001b;Chance et al, 2006). These studies demonstrate that humans have larger minicolumns than other smaller mammals.…”
mentioning
confidence: 90%
“…The details of this columnar neuronal circuitry have been particularly well described for the primary visual cortex. Within the visual cortex, each cortical column receives information from each eye in an alternating (left eye, right eye) pattern (Mountcastle, 1997;Gurshumov and Yinon, 2005). Additionally, detailed studies are widely available for the somatosensory cortex, auditory cortex, and motor cortex (Mountcastle, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a considerable number of studies have reported minicolumn spacing for a variety of smaller mammals: rhesus macaque temporal cortex (Buxhoeveden and Casanova,2000; Buxhoeveden et al,2001a,b); rhesus macaque motor cortex (Amirikian and Georgopoulos,2003); cat primary somatosensory cortex (Favorov and Diamond,1990; Tommerdahl et al,1993); cat visual cortex (Gurshumov and Yinon,2005); rat somatosensory cortex (Tommerdahl et al,1993; Joublin et al,1996; Lubke and Feldmeyer,2007), and for humans: cingulate and pericingulate cortex (Schlaug et al,1995); primary auditory cortex (Chance et al,2006); posterior auditory association region (Buxhoeveden and Casanova,2000; Buxhoeveden et al,2001b; Chance et al,2006). These studies demonstrate that humans have larger minicolumns than other smaller mammals.…”
mentioning
confidence: 98%